2016
DOI: 10.1075/resla.29.2.01vil
|View full text |Cite
|
Sign up to set email alerts
|

Early null and overt subjects in the Spanish of simultaneous English-Spanish bilinguals and Crosslinguistic Influence

Abstract: This study assesses the scope of the Crosslinguistic Influence (CLI)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Then, the first category, lexis, explored L2 code switch (Bullock & Toribio, 2009), use of false friends or cognates, and calques 2 , both from the target language (Burton, 2013;Muñoz-Basol & Salazar, 2016). The second category, syntax, examined whether there were examples of L2 word order (as in adjective+noun, rather than noun+adjective from the L1, Spanish) (Morett & MacWhinney, 2013), use of elliptical/covert subjects, frequent in the L1 but not in the L2 (Balcom, 2003;Villa-García & Suárez-Palma, 2016), and finally, phrase calques, involving a direct translation from a phrase or sentence from the L2 (Riera & Romero, 2010). Results are shown in Table 7, below.…”
Section: Resultsmentioning
confidence: 99%
“…Then, the first category, lexis, explored L2 code switch (Bullock & Toribio, 2009), use of false friends or cognates, and calques 2 , both from the target language (Burton, 2013;Muñoz-Basol & Salazar, 2016). The second category, syntax, examined whether there were examples of L2 word order (as in adjective+noun, rather than noun+adjective from the L1, Spanish) (Morett & MacWhinney, 2013), use of elliptical/covert subjects, frequent in the L1 but not in the L2 (Balcom, 2003;Villa-García & Suárez-Palma, 2016), and finally, phrase calques, involving a direct translation from a phrase or sentence from the L2 (Riera & Romero, 2010). Results are shown in Table 7, below.…”
Section: Resultsmentioning
confidence: 99%
“…The development of subjects in bilingual children is typically researched through corpus studies on Spanish-English bilingual children (with generally very few subjects), and the focus has generally been on the proportion of overt subjects in the children's Spanish, which some studies have shown to be higher in bilingual children than in monolingual children (e.g., Paradis and Navarro 2003;Villa-García and Suárez-Palma 2016).…”
Section: Word Order In Child Heritage Speakersmentioning
confidence: 99%
“…An anonymous reviewer noted that, according toVilla-García & Suárez-Palma (2016), the cross-linguistic influence and the interface hypothesis may not play a part in the acquisition of subjects in terms of rate of overt and null subjects, preverbal and post-verbal subjects, as well as their pragmatic felicitousness. Their study is based on different corpora and it involves four English-Spanish bilingual children and one Spanish monolingual child.…”
mentioning
confidence: 99%